Molecular Breeding for Biotic and Abiotic Stress Resistance in Vegetable Crops - Singamayum Ashif (Global Journal of Plant and Soil Sciences, 2025)
Molecular breeding, utilizing molecular markers, holds immense promise in revolutionizing plant breeding programs, particularly in the context of vegetable crops. This approach necessitates appropriate marker systems, mapping populations, and software for genotypic data analysis. DNA markers, offering insights into genetic variations unaffected by environmental factors, are pivotal in crop improvement efforts. Vegetable crops, heralded as protective foods due to their richness in essential vitamins and minerals, play a crucial role in addressing malnutrition, especially among children in India. Despite India's status as the second-largest producer of vegetable crops globally, productivity remains constrained, with per capita availability significantly lower than in developed na- tions. Biotic and abiotic stresses contribute substantially to yield reduction, with losses attributed to insects, weeds, diseases, and pathogens. Traditionally, classical breeding methods have been employed to develop resistance in vegetable crops against biotic stresses. However, these approaches suffer from limitations such as slow progress, high costs, and issues of linkage drag. In response, molecu- lar genetics techniques have been embraced, offering faster and more precise methods for developing resistance traits. DNA mark- ers, in particular, facilitate marker-assisted selection (MAS), enhancing breeding efficiency by streamlining screening procedures. Moreover, abiotic stresses like drought, salinity and temperature extremes pose significant challenges to vegetable crop productivity. Many plant species have evolved resistance mechanisms against these stresses, and molecular tools provide avenues for deciphering these mechanisms and transferring resistance traits to cultivated varieties.